Manifestaciones epidemiológicas y clínicas de la meningitis bacteriana en niños - Segura Chávez, Andy Denis (2016)
Introduction: Bacterial Meningitis (MB) is a disease with high morbidity and mortality resulting from bacterial infection of leptomeningeal that mostly affects children under 5 years. Objective: To describe the epidemiological and clinical characteristics of bacterial meningitis in children manifestations. Material and Methods: Observational, descriptive and retrospective study. From 87 HC: medical records (HC) of older children 1 month and under 18 years diagnosed with MB, hospitalized in the pediatric ward of the Regional Hospital of Trujillo between January 1993 to December 2014. Results: were reviewed, 46 met the inclusion criteria. The 56.52% were female. The most frequent age range was 1 to 11meses (52.17%) and was the largest source Trujillo (67.19%). The most common symptoms were fever (95.7%), rejection of food (84.8%) and vomiting (63%); and the most common signs were altered consciousness (75%), seizures (60.9%) and irritability (63%). Gram in the cerebrospinal fluid (CSF) Gram + lanceolate diplococci identified in 35, 95% and CSF culture were more frequent Streptococcus pneumoniae (26.09%) and Haemophilus influenzae (21.74%). Conclusions: Age, symptoms, signs in our study had results similar to traditional studies gender variable except where the female predominance. Pneumococcus was the most frequent agent